2011
DOI: 10.1016/j.resp.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Vagal afferents modulate cytokine-mediated respiratory control at the neonatal medulla oblongata

Abstract: Perinatal sepsis and inflammation trigger lung and brain injury in preterm infants, and associated apnea of prematurity. We hypothesized that endotoxin exposure in the immature lung would upregulate proinflammatory cytokine mRNA expression in the medulla oblongata and be associated with impaired respiratory control. Lipopolysaccharide (LPS, 0.1 mg/kg) or saline was administered intratracheally to rat pups and medulla oblongatas were harvested for quantifying expression of mRNA for proinflammatory cytokines. LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 45 publications
1
49
0
Order By: Relevance
“…A study in rat pups demonstrated that systemic exposure to lL-1β decreased respiratory activity in response to hypoxia while another study showed similar hypoxic respiratory depression in the context of intra-tracheal administration of LPS (Balan et al 2011; Olsson et al 2003). Maternal and fetal pro-inflammatory stimuli can also initiate signaling cascades through HIF-1α.…”
Section: Intersection Of Hypoxia and Hyperoxia With Systemic Inflammamentioning
confidence: 97%
“…A study in rat pups demonstrated that systemic exposure to lL-1β decreased respiratory activity in response to hypoxia while another study showed similar hypoxic respiratory depression in the context of intra-tracheal administration of LPS (Balan et al 2011; Olsson et al 2003). Maternal and fetal pro-inflammatory stimuli can also initiate signaling cascades through HIF-1α.…”
Section: Intersection Of Hypoxia and Hyperoxia With Systemic Inflammamentioning
confidence: 97%
“…We have recently shown that rat pups exposed to intratracheal lipopolysaccharide demonstrate increased expression of mRNA for the proinflammatory cytokines IL-1 ␤ and IL-6 in the brainstem. This is associated with an attenuated ventilatory response to hypoxia, both before and after carotid sinus nerve transection [17] . This is consistent with prior data that endotoxemia impairs the ventilatory response to hypoxia in rat pups [18] , and that prostaglandin-mediated respiratory inhibition may be implicated [19] .…”
Section: Intermittent Hypoxia As a Proinflammatory Stressmentioning
confidence: 99%
“…Since the capacity for LPS penetration across the BBB is low (Banks and Robinson, 2010), recent research has highlighted multiple alternative transmission mechanisms. Even low-dose LPS (intraperitoneal or intratracheal) is sufficient to induce inflammatory gene and protein expression in the CNS without significant levels of LPS crossing the BBB (Balan et al, 2011; Banks and Robinson, 2010; Laye et al, 1995). Vagal afferents moderate communication of low-level systemic inflammation to the CNS, since vagotomy eliminates the febrile response associated with sickness and inflammation after very low doses of LPS (1ug/kg), but not higher doses.…”
Section: Models Of Inflammationmentioning
confidence: 99%